Borehole Dimension Impact on LHD Operation in Malmberget Mine - Danielsson, Markus (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2016)
Sublevel caving is a highly mechanizable mass mining method normally utilized in large, steeply dipping orebodies. The fragmented ore flows freely, aided by gravity, down to the drawpoint while the surrounding waste rock caves in due to induced stresses and gravity. Fragmentation of the blasted ore is a vital component in any mining operation and directly affects productivity and efficiency of the following production steps (Nielsen et. al, 1996). In an attempt to reduce mining induced seismicity in Malmberget, LKAB is initiating various trials. One of these trials involves a reduction in blasthole dimension and an increase in the number of blastholes utilized in each ring. A reduction in blasthole dimension is undertaken to achieve a less impactful mining operation in terms of disturbances to surface populated areas, particularly addressed to ground vibrations. Therefore, it is of utmost importance to analyse if fragmentation and production is affected as a consequence of this change. This thesis sets out to evaluate how fragmentation and the LHD operation is affected by variations in blasthole dimension. The evaluation is carried out through analysis of logged production data, on-site filming of the loading sequence and interviews with the LHD operators. The discoveries will be presented chronologically to illustrate the complexities related to compiling a viable dataset to rely on for a credible analysis. The initial theory did not hold up properly and therefore the project was reshaped along the course of progression to provide further information and clarify uncertainties. Unfortunate, major production delays inhibited a quantitative comparison of two parallel drifts with different blasthole dimensions. Hence, no final answer can be provided in this thesis whether a change in blasthole dimension causes any differences in loadability and/or fragmentation or not. However, an analysis of how cycle times vary depending on causes such as operator induced differences, machine induced differences and road ...